An Assessment of School Plant Management and Covid-19 Mitigation for Quality Assurance: Experience From Kwara State - Oluwatoyin, Fashiku Christopher; Abiola, Yusuf Abubakar; Baba, Ayoku Oba (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The study assessed school plant management and COVID-19 mitigation for quality assurance in Kwara State public primary schools. In the study, a descriptive survey research design was used. In Kwara State public primary schools, 390 teachers were chosen using a multistage sampling technique. The study used a self-designed and validated questionnaire titled